Super-Minimal Incision Technique in Pediatric Kidney Transplantation: A Paired Kidney Analysis - Wang, Junxiang; Zhao, Lixiang; Feng, Guiwen; Shang, Wenjun (Frontiers in Pediatrics, 2022)
Background: Recently, the demand for minimally invasive techniques in kidney transplantation (MIKT) has increased, but there is only a limited number of studies on MIKT, especially in pediatric kidney transplants. Hence, we evaluated whether there is a difference between the super-minimal incision technique in pediatric kidney transplantation (SMIPKT) and conventional kidney transplantation (CKT). Methods: Between December 2018 and November 2021, 34 patients who underwent pediatric kidney transplantation with a follow-up of 1 month were enrolled. A paired kidney analysis was performed to minimize donor variability and bias. The SMIPKT and CKT groups included 17 patients. Results: There was no difference in baseline clinical characteristics, including age, sex, choice of dialysis modality, pretransplant dialysis time, BMI, renal artery number, cause of ESRD, DGF, length of the kidney and cold ischemic time, tacrolimus concentration at 3 days and 7 days, serum creatinine at 1 month and postoperative complication rate between the SMIPKT and CKT groups (all P>0.05); however, the length of the incision, operation time, intraoperative bleeding, postoperative drainage volume within 24 hours, and Vancouver scar scale at 1 month were statistically significant (all P<0.05). Conclusion: Compared with CKT, our results indicated that SMIPKT showed more satisfactory cosmetic results, shorter SMIPKT operating time, and reduced intraoperative bleeding and postoperative drainage volume within 24 hours, and there were no statistical differences in postoperative complications. Hence, we suggest that SMIPKT is an appropriate method for pediatric kidney transplantation.